Two new species of Frankliniella (Thysanoptera: Thripidae) from Argentina with a key to species from Argentina and Chile - Borbón, Carlos Manuel De; Zamar, María Inés (Zootaxa, 2018)
A key is provided to 27 species of Frankliniella recorded from Argentina and Chile. Two new species are described from Argentina: Frankliniella inesae sp. n. from Baccharis [Asteraceae] and Frankliniella juancarlosi sp. n. from Junellia [Verbenaceae]. Two species are newly recorded from Argentina: Frankliniella condei John and Frankliniella longipennis (Moulton). Pore plates on sternite III of females and a vestigial craspedum on tergite VII are used as diagnostic characters.